Can Pulsed Electric Fields Treated Algal Cells Be Used as Stationary Phase in Chromatography? - Pleissner, Daniel; Smetana, Sergiy (Frontiers in Sustainable Food Systems, 2022)
Microalgae are utilized for various purposes through cell content extraction and application. Cell walls are not utilized and not studied in an extensive manner. At the same time, composition of multilayer and fibrillar structures with various chemical compositions depends on microalgae species, they present an interesting object for chromatography. However, it requires the application of novel processing technologies (such as pulsed electric fields [PEFs]), which are able to selectively permeabilize the cell walls with pores of various sizes and shapes. The current review indicates the application of potential of microalgae cell walls for separation by size exclusion, ion-exchange, and hydrophobic interaction chromatography. However, such a hypothesis should be further experimentally proven.